President’s Message - Ferguson, Cathleen (Operating Room Nurses Association of Canada Journal, 2016)
A simple definition of passion, according to the Merriam- Webster dictionary, is “a strong feeling of enthusiasm or excitement for something or about doing something”. As ORNAC President I have had the extraordinary experience of meeting perioperative nurses from all across Canada. They are strong, spirited, and positive even in the face of difficult and stressful times.